Optimization of Local Original Revenue (PAD) through Regional Tax Revenue of North Kalimantan Province - Indriani, Henny; Muktiyanto, Ali; Azis, Musdalifah (IJEBD (International Journal of Entrepreneurship and Business Development), 2024)
Purpose: to analyze the effect of local tax revenue targets, regional tax intensification and intensification costs and management of regional tax receivables on the optimization of regional revenues of the North Kalimantan Provincial Government Design/methodology/approach: quantitative research by taking the object of research at the Regional Revenue Agency of North Kalimantan Province in Tanjung Selor City. The analysis techniques used use multiple linear regression analysis, t-test and determination coefficient analysis Findings: the variable target of regional tax revenue has a positive and significant influence on the optimization of local original revenue of North Kalimantan Province in 2015-2022. The variable costs of intensification and extensification do not have a significant influence on the optimization of local native income of North Kalimantan Province in 2015-2022. The variable of regional tax receivables management has a negative and significant influence on the optimization of local original revenue of North Kalimantan Province in 2015-2022. Practical implications: Intensifying local tax revenue targets, local tax intensification and intensification costs and managing regional tax receivables towards optimizing local revenues of the North Kalimantan Provincial Government. Originality/value: This paper is original Paper type: research paper